The psychology of appraisal: Specific emotions and decision‐making - So, Jane; Achar, Chethana; Han, DaHee; Agrawal, Nidhi; Duhachek, Adam; Maheswaran, Durairaj (Journal of Consumer Psychology, 2015)
AbstractA growing stream of research has examined emotions and decision‐making based on the appraisal tendencies associated with emotions. This paper outlines two general approaches that can lead to further our understanding of the variety of ways emotions affect decision‐making and information processing. Specifically, future research can examine the nature of emotional appraisals or investigate the nature of decision contexts and underlying psychological processes influenced by emotions. To understand the nature of emotional appraisals, scholars could examine the interaction of two appraisal dimensions or identify novel appraisal tendencies. To understand the decision‐making contexts and psychological processes influenced by emotions, scholars could examine how emotions interact with contextual influences to shape judgments through a variety of processes such as providing information, priming goals, or activating mindsets. These approaches to the study of emotions and decision‐making will contribute to more nuanced theory development around emotions, nurture new empirical work, and encourage interest in exploring a broader set of emotions.